Budget Allocation Strategies for Educational Expenses of Grade 12 General Academic Strand Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focuses on how students will enhance their allowances by using budget allocationstrategies. One of the most common problems of Grade 12 general academic strand studentsis that they are unaware of their daily expenditures. They lack knowledge about how toproperly organize their budget and manage their spending.Based on the result of the study, using budget allocation strategies for educational expensespositively affected the budget management of Grade 12 GAS students in terms of (1) foodallowances (38% of their allowances were allocated to food), (2) school supplies (34% of theirallowances go to school materials and buying unnecessary things), and (3) external projects(28% go to program tickets that are not school-related and mismanagement of allowance).Based on the summary of the findings, the following recommendations were made by theresearchers on how Grade 12 GAS students should allocate their allowances.
Keywords: Education